Economic Factors Affecting Imports Per Capita in Indonesia: Empirical Evidence from the Error Correction Model - Prawoto, Nano (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of economic factors on the per capita import of goods and services in Indonesia, focusing on GDP per capita, consumption per capita, population, value added of the manufacturing sector, international trade taxes, and exchange rates. Using annual data from the World Development Indicator for the period 1989 to 2023, the analysis was carried out using the dynamic Error Correction Model (ECM). The results show that in the long run, imports per capita are significantly influenced by GDP per capita, consumption per capita, population, added value of the manufacturing sector, and international trade taxes. However, the exchange rate does not show a significant influence on imports per capita in Indonesia. In contrast, in the short term, changes in GDP per capita, consumption per capita, exchange rate, and the added value of the manufacturing sector have a significant influence on changes in imports, while population size and international trade taxes have no significant effect. These findings have important implications for Indonesia's economic policy, particularly in trade policy planning and management of the manufacturing sector, as well as for designing strategies to increase economic independence by considering factors affecting imports. The main contribution of this research is to provide empirical insights that can be used by policymakers in formulating more effective trade and economic development policies, as well as providing a basis for further research on the relationship between macroeconomic variables and imports